STUDENTS’ PERCEPTIONS OF GRAMMARLY AS AN AI-ASSISTED WRITING TOOL IN ACADEMIC WRITING - Khanifatin; Kurniawati, Dyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growing use of artificial intelligence in language learning has encouraged the development of digital tools that support academic writing, and Grammarly is one of the most widely used applications. This study explored EFL students’ perceptions of Grammarly as an AI-assisted writing tool in academic writing. A qualitative case study was conducted with seventeen fourth-semester students from the English Language Education Study Program at Universitas PGRI Ronggolawe Tuban during the 2025/2026 academic year. Data were collected through classroom observation, questionnaires, and semi-structured interviews, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that students generally perceived Grammarly positively because it helped them identify grammatical errors, improve sentence structure, and revise writing more efficiently. Grammarly also increased students’ confidence and supported more independent learning through immediate feedback. However, participants also reported several challenges, including inaccurate suggestions, dependence on internet connectivity, and the need to evaluate AI-generated feedback critically. The study concludes that Grammarly is a useful complementary tool that should support, not replace, instructors’ guidance. Integrating Grammarly into EFL writing instruction with appropriate pedagogical support may help improve students’ academic writing skills and promote learner autonomy.